Retrospective Assessment of Antibiotics Prescribing at Public Primary Healthcare Facilities in Addis Ababa, Ethiopia. (28th February 2018) - Worku, Fikru; Tewahido, Dagmawit
Abstract : Background. Antibiotic overprescribing is the major driving force for the emergence of antibiotics resistance. The aim of this study was to assess antibiotics prescribing at primary healthcare facilities in Addis Ababa, Ethiopia. Methods. The study was conducted in six public health centers found in Addis Ababa City. Data was collected retrospectively from a total of 900 prescriptions and selected medical charts of patients in the health centers in 2016. Data was entered and analyzed using EPI Info 7 and SPSS 20, respectively. Descriptive statistics and logistic regression analysis were used to analyze the data. Results. One or more antibiotics were prescribed in 56.0% of the prescriptions. Antibiotics accounted for 46.0% of the total cost of medicines prescribed. Amoxicillin was the most frequently (44.8%) prescribed antibiotic and upper respiratory tract infection was the most common (24.5%) diagnosis for prescribing antibiotics. Laboratory investigation was done for only about 27% of the cases for which antibiotics were prescribed. Conclusion. There was a high rate of antibiotics prescribing in the health centers often empirically which might exacerbate the antimicrobial resistance situation in the country. Large-scale study should be conducted to fully understand the prescribing pattern and identify the associated factors thereby design and implement appropriate interventions.